PEMANFAATAN Lactobacillus casei DAN TAPIOKA DALAM UPAYA MENGHAMBAT KERUSAKAN TEMPE KEDELAI - Lidya Tri Aptesia; Suharyono -; Harun Al Rasyid (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
The objective of this research was to test the effectivenes on the use of L.casei and tapioca as the addition nutrition to prevent the damage of soy tempeh. The experiment was arranged in a complete randomized block design consisted of two factors and 3 replications. The first factor was the concentration of L.casei (0%, 1%, 1,5%, and 2%), the other factor was the concentration of tapioca (0%, 0,4%, 0,8%, and 1,2%). The data were analyzed with analysis of variance then continued with Honestly Significant Differences Test (HSD Test) with significance level of 5% and 1%. The result showed that the concentration of L.casei 2% and tapioca 0,8% was able to prevent the tempeh deterioration. The shelf-life reached 9 days of storage, the product had a longer shelf-life compared to that of the control (soy tempeh with no treatment) which only had 3 days of shelf life. Key word : Lactobacillus casei, soybean, tapioca, tempeh